Multi-element metal hydroxide self-supporting integrated activation electrode and preparation and application thereof

Through the preparation and constant current activation of multi-metal hydroxide self-supported integrated activation electrode, the problem of insufficient activity and stability of OER electrodes is solved, and the low-energy consumption and high-efficiency electrolysis hydrogen production process is achieved, and the electrolysis technology is improved. Competitiveness.

CN119121282AActive Publication Date: 2024-12-13HUNAN NORMAL UNIVERSITY +2

Patent Information

Application Number
CN202411050004.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2024-12-13
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

The catalytic activity and high current catalytic stability of the existing OER electrodes are not ideal, resulting in high energy consumption in the electrolytic hydrogen production process, limiting its competitiveness in large-scale applications.

Method used

The preparation method of a multivariate metal hydroxide self-supported integrated activation electrode is adopted. The high entropy hydroxide is formed by combining the support and dissolved metal elements. To improve OER activity and high current cycle stability.

Benefits of technology

It significantly reduces the overpotential of the OER process, improves the activity and stability of the catalyst, can run for a long time under high current density without deactivation, and improves the efficiency and cost competitiveness of electrolyzed hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121282A_ABST
    Figure CN119121282A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrolyzed water, and particularly relates to a preparation method of a multi-element metal hydroxide self-supporting integrated activation electrode, which comprises the following steps: compounding a metal hydroxide on a carrier to prepare an electrode precursor; the metal hydroxides comprise hydroxides of metal elements of metals M1, M2 and M3; wherein M1 comprises at least one of Fe, Co and Ni; m2 comprises at least one of Be, Al, Zn, Ga, In, Sn, Sb, Tl, Pb, Bi, Cr and Mn; m3 comprises at least one of Cu, Sc, Ti, V, Mo, W, Ru, Rh, Pd, Ag, Cd, Au, Pt and Ir; and performing constant-current activation on the electrode precursor under the current density of more than 200mA / cm < 2 > to prepare the multi-element metal hydroxide self-supporting integrated activation electrode. The invention also comprises the material prepared by the preparation method and application of the material in OER catalysis. The process provided by the invention can improve the OER activity and large-current cycling stability of the prepared electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalysis, and in particular relates to the field of OER electrocatalytic electrodes. Background Art

[0002] Hydrogen can be used as an energy carrier for energy conversion and storage. Hydrogen can be produced in a variety of ways, the most common of which is water electrolysis, which uses electricity to decompose water into hydrogen (H2) and oxygen (O2). This process can be powered by renewable energy (such as wind or solar energy), so that the production process of hydrogen can be zero-carbon or low-carbon. At the same time, hydrogen has a high energy density, which can provide more possibilities for long-term energy storage.

[0003] At present, the technology of hydrogen production by water electrolysis has been widely used. Water electrolysis can be divided into two half reactions, namely the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Since the oxygen evolution reaction (OER) on the anode side is a four-electron transfer process, its kinetics are slow compared to the hydrogen evolution reaction (HER) on the cathode side. When the same current density is obtained, the OER process requires a higher overpotential, which increases the energy consumption in the water electrolysis process. The large amount of electrical energy input in the process of water electrolysis, especially when large-scale hydrogen is produced, has high energy consumption. This leads to a high cost of water electrolysis technology, limiting its competitiveness in large-scale applications. Therefore, it is particularly important to reduce the overpotential of the OER process.

[0004] Traditionally, platinum group metals such as iridium (Ir) and platinum (Pt) are considered to be efficient OER catalysts, but they are expensive and scarce, which limits their large-scale application. Therefore, researchers are actively looking for cheap and efficient alternative materials. Common alternative catalysts include transition metal oxides (such as nickel oxide, molybdenum oxide, iron oxide, etc.) and hydroxides (such as cobalt oxide, nickel hydroxide, etc.), as well as nitrogen-doped carbon materials. How to further improve the activity and stability of these relatively cheap catalysts in all aspects is particularly important. In addition, there are also some reports on metal hydroxide OER materials in the prior art, but the OER performance of these technologies and the stability under high current still need to be improved. Summary of the invention

[0005] In view of the problems of unsatisfactory catalytic activity and high-current catalytic stability of existing OER electrodes, the first purpose of the present invention is to provide a method for preparing a self-supporting integrated activated electrode of a multi-metal hydroxide, aiming to obtain an OER electrode with both excellent OER catalytic activity and high-current catalytic stability.

[0006] The second object of the present invention is to provide a multi-metal hydroxide self-supporting integrated activated electrode prepared by the preparation method and its application in electrocatalysis.

[0007] A method for preparing a multi-metal hydroxide self-supporting integrated activated electrode, comprising compounding metal hydroxides on a carrier to obtain an electrode precursor; the metal hydroxides include hydroxides of metal elements M1, M2 and M3; wherein M1 includes at least one of Fe, Co and Ni; M2 includes at least one of Be, Al, Zn, Ga, In, Sn, Sb, Tl, Pb, Bi, Cr and Mn; and M3 includes at least one of Cu, Sc, Ti, V, Mo, W, Ru, Rh, Pd, Ag, Cd, Au, Pt and Ir;

[0008] Then the electrode precursor was charged at 200 mA / cm 2 Constant current activation is carried out at a current density above 500 nm to obtain a multi-metal hydroxide self-supporting integrated activated electrode.

[0009] The innovative research of the present invention shows that by innovatively subjecting the multi-component composite hydroxide containing metals M1-M2-M3 to constant current activation under the high current, the influence of the high current on the structure and OER degradation can be avoided, and instead the multi-component composite hydroxide can be promoted to undergo beneficial physicochemical transformation, which can unexpectedly enable it to have excellent OER activity and high current cycling stability.

[0010] In the present invention, the multi-metal hydroxide and its constant current activation and the joint control of current are the key to inducing the physicochemical transformation of the active ingredients and improving their OER activity and high current performance.

[0011] In the present invention, the carrier can be a component that can be used as an electrode material that is well known in the OER field, for example, at least one of porous metals, porous carbon materials, and silicon-based materials; further at least one of foamed nickel, foamed copper, foamed titanium, carbon materials, silicide graphene, and molecular sieves.

[0012] In the present invention, the types of the metal elements in the metal hydroxide are more than 5. The present invention shows that the innovative use of more than 5 metal elements including M1 / M2 / M3 to form a high entropy hydroxide, combined with the subsequent high current constant current activation of the present invention, can further construct the subsequent OER-adaptive physicochemical characteristics, and can improve the OER activity and high current catalytic stability of the prepared material.

[0013] Preferably, the metal M1 includes Fe, Co and Ni; preferably, the molar ratio is 1-4:2-4:2-4; further, it can be 1:2-2.5:2-2.5.

[0014] In the present invention, the M2 may be at least one of Al and Cr.

[0015] The M3 may be Cu.

[0016] In the present invention, in the metal hydroxide, the molar ratio of the metals M1, M2 and M3 is 1-8:1-4:1-4; further, it can be 4-6:1:2-3.

[0017] In the present invention, the support and the metal solution of the dissolved metals M1, M2 and M3 are compounded, and then dried and alkali precipitated to obtain the electrode precursor;

[0018] Preferably, in the metal solution, the total metal concentration is 0.1 to 4 M, for example, further can be 0.5 to 2 M;

[0019] Preferably, the metal solution is compounded with the carrier by a spraying method. The present invention shows that the metal solution and the carrier are compounded by the spraying method, which can be further combined based on the metal element and high current constant current activation, which can further facilitate the construction of OER-compatible physicochemical characteristics and help to further enhance its OER activity and catalytic stability.

[0020] Preferably, the alkali solution used in the alkali precipitation is an aqueous solution of alkali metal hydroxide;

[0021] Preferably, the concentration of the alkali metal hydroxide in the alkali solution is above 0.5M; further, 0.5-2M.

[0022] In the present invention, the precursor electrode is activated in an alkaline solution with constant current;

[0023] Preferably, the alkali solution is an alkali metal hydroxide aqueous solution with a concentration of 0.5M or more, preferably 0.5-5M, and further can be 1-2M;

[0024] Preferably, the constant current activation method is a single-electrode, double-electrode or three-electrode method.

[0025] In the present invention, the current density in the constant current activation stage is 500 mA / cm 2 Above, further 500mA / cm 2 ~1500mA / cm 2 The present invention shows that under the optimal current density, it is further beneficial to construct the physical and chemical characteristics of OER catalytic adaptation, which can further enhance the OER activity and catalytic stability of the material.

[0026] In the present invention, the constant current activation time is 10 minutes or more, preferably 10 to 600 minutes, and can be further 20 to 50 minutes in consideration of efficiency.

[0027] The present invention also provides a multi-metal hydroxide self-supporting integrated activation electrode prepared by the preparation method.

[0028] In the present invention, thanks to the preparation method, the physical and chemical characteristics suitable for OER can be constructed, and the material with the characteristics prepared by the preparation method has both excellent OER performance and catalytic stability.

[0029] The present invention also provides the use of the multi-metal hydroxide self-supporting integrated activation electrode prepared by the preparation method, which is used as an OER catalytic anode for electrocatalysis;

[0030] Furthermore, the electrocatalysis is at least one of aqueous solution electrocatalysis, carbon dioxide electrocatalytic reduction, and nitrogen fixation electrocatalysis;

[0031] Preferably, the aqueous solution is an alkaline aqueous solution.

[0032] Beneficial effects:

[0033] The present invention innovatively subjects the multi-component composite hydroxide containing metals M1-M2-M3 to constant current activation under the large current, thereby avoiding the influence of large current on deterioration and promoting beneficial physicochemical transformation of the multi-component composite hydroxide, which unexpectedly enables it to have excellent OER activity and large current cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the SEM image of the unactivated FeCoNiCrCu electrode prepared in step 1 of Example 1.

[0035] Figure 2 The current density of step 2 in Example 1 is 1A / cm 2 SEM image of FeCoNiCrCu electrode after activation for 30 min. The layered structure is still connected in a scale-like manner, but the surface is reconstructed under high current stimulation, the specific surface area increases, and the number of active sites increases.

[0036] Figure 3 LSV diagrams of the FeCoNiCrCu electrode after activation in Example 1 and the FeCoNiCrCu electrode after activation in Group A of Example 3.

[0037] Figure 4 The FeCoNiCrCu self-supporting integrated activated electrode after activation in Example 1 is 1A / cm 2 Stability test diagram under current density.

[0038] Figure 5 The NiAlCu after activation in Example 2 is 1A / cm 2 LSV diagram after activation for 30 min at current density;

[0039] Figure 6 For FeCoNiCrCu at 20mA / cm 2 LSV diagram after activation for 30 min at current density

[0040] Figure 7 This is the SEM image of the FeCoNiCrCu electrode after activation in Example 3B group.

[0041] Figure 8 LSV diagram of OER activity of nickel foam in comparative example 1;

[0042] Fig. 9 is the LSV diagram of comparative example 2FeCoNiCrCu after CV activation; DETAILED DESCRIPTION

[0043] Example 1

[0044] Step (1): Preparation of electrode precursor

[0045] Dissolve 606mg (1.5mmol) of ferric nitrate nonahydrate, 874mg (3mmol) of cobalt nitrate hexahydrate, 873mg (3mmol) of nickel nitrate hexahydrate, 601mg (1.5mmol) of chromium nitrate nonahydrate, and 725mg (3mmol) of copper nitrate hexahydrate in 10ml of methanol and stir for 1h to form a uniform salt solution. Place a 1cm×1.5cm nickel foam in 1mol / L hydrochloric acid and ultrasonicate for 30min, then wash it with clean water and dry it in a vacuum oven. Take 100ul of the salt solution and use a spray gun to spray it evenly on a 1cm×1cm area of ​​the nickel foam and dry it. After drying, immerse the nickel foam in a 1mol / L KOH solution. Obtain the FeCoNiCrCu composite high entropy hydroxide OER catalyst precursor (SEM see Figure 1 ).

[0046] Step (2): Activation

[0047] It was directly used as the working electrode and then 2 The activation process was carried out under constant current density to obtain a highly active and stable OER catalyst. The activation environment was carried out in a normal three-electrode system, with the mercury / mercuric oxide electrode as the reference electrode, the Pt sheet electrode as the counter electrode, the electrolyte as 1M KOH, and the activation time as 30 min. A self-supporting integrated activated electrode was obtained (SEM see Figure 2 ).

[0048] Step (3): OER testing

[0049] The activated electrode prepared in step 2 was placed in a three-electrode system for LSV test and stability test, and the test environment was room temperature. The electrode was used as the working electrode, the mercury / mercury oxide electrode was used as the reference electrode, the Pt sheet electrode was used as the counter electrode, and the electrolyte was 1M KOH. The electrochemical workstation was a Gamry electrochemical workstation, model: Interface 1010E.

[0050] The LSV test parameter settings were as follows: voltage range was 0.2-1.5 V, scan speed was 5 mV / s, automatic IR compensation was used, and starting from a low potential, the OER overpotential of the electrode was obtained at a current density of 500 mA / cm2.

[0051] Stability test parameter setting: The stability test uses the chronovoltage method and sets the current density to 1A / cm 2 . Add water regularly to keep the electrolyte concentration constant.

[0052] OER performance test and results:

[0053] LSV data analysis, for the convenience of comparison, the potential relative to mercury / mercury oxide is converted to the potential relative to the standard hydrogen electrode (RHE), and its OER performance is shown in Figure 3 , at 500mA / cm 2 The OER overpotential at this current density is only 312.7 mV, which is 50.4 mV lower than that before activation.

[0054] At 1A / cm 2 The stability of the electrode was verified by a timed voltage test under current density of 1A / cm 2 The OER catalytic performance did not change significantly after running for 3000 hours at the current density, indicating its ultra-long catalytic stability and catalytic activity. The actual working voltage is converted to a potential of about 1.6V relative to the standard hydrogen electrode (RHE). (After IR compensation of the stability test data, the fluctuation of the curve is mainly caused by temperature difference and water addition during the stability test). Figure 4 .

[0055] Embodiment 2:

[0056] Compared with Example 1, the only difference is that the type and ratio of the metal in the precursor metal are changed.

[0057] The metal elements in the electrode precursor are Ni, Al, and Cu (three metals) with a molar ratio of 3-2-3; the activation time is 40 minutes, and the amount of total metal elements and other operations and parameters are the same as in Example 1.

[0058] The activation and testing were carried out according to the method of Example 1. The results were as follows: the performance after activation was better than before activation. The overpotential of OER at a current density of 500 mA / cm2 was 446 mV. The overpotential of OER after activation was still 48 mV lower than that before activation, indicating the effectiveness of activation. Figure 5 .

[0059] Example 3: Changing the current of constant current activation

[0060] Compared with Example 1, the only difference is that the current density of the constant current activation in step 2 is changed. The experimental groups are:

[0061] Group A: current density is 500mA / cm2;

[0062] Group B: current density 20mA / cm2;

[0063] Activation and testing were performed according to the method of Example 1, and the results were:

[0064] Group A: at 500mA / cm 2 The OER overpotential at this current density is 337.6 mV, which is 25.5 mV lower than that before activation. Figure 3 .

[0065] Group B: at 500mA / cm 2 The OER overpotential at the current density is 355.3mV, which is 7.8mV lower than before activation, with little change. Figure 6 , SEM characterization results are as follows Figure 7 .

[0066] Comparative Example 1:

[0067] Compared with Example 1, the only difference is that steps 1 and 2 are omitted, and the nickel foam is directly used as the working electrode to carry out the OER test, and a blank control is carried out.

[0068] The OER test was carried out according to the method of Example 1, and the results were:

[0069] At 500mA / cm 2 The OER overpotential at the current density is 679.8 mV, indicating that the integrated activated electrode prepared by this method can significantly reduce the OER overpotential. Figure 8 .

[0070] Comparative Example 2:

[0071] Compared with Example 1, the difference is that the activation method of step 2 is changed, that is, a large constant current activation is not used, but a CV cycle method is used for activation. The CV activation parameters are set as follows: the voltage range is 0.2-1.2V (without IR compensation), the scanning speed is 100mV / s, and the cycle scan is 50 circles. The curves are stably overlapped, indicating that the effective value of CV activation has been basically reached.

[0072] The OER test was carried out according to the method of Example 1, and the results were:

[0073] 500mA / cm 2 The OER overpotential at the current density is 341.1 mV. CV activation also improves the activity of the catalyst, but the effect is not as obvious as that of high current activation. Fig. 9 .

Claims

1. A method for preparing a self-supporting integrated activated electrode of a multi-metal hydroxide, characterized in that: Composite metal hydroxides on a carrier to obtain an electrode precursor; the metal hydroxides include hydroxides of metal elements M1, M2 and M3; wherein M1 includes at least one of Fe, Co and Ni; M2 includes at least one of Be, Al, Zn, Ga, In, Sn, Sb, Tl, Pb, Bi, Cr and Mn; and M3 includes at least one of Cu, Sc, Ti, V, Mo, W, Ru, Rh, Pd, Ag, Cd, Au, Pt and Ir; Then the electrode precursor was charged at 200 mA / cm 2 Constant current activation is carried out at a current density above 500 nm to obtain a multi-metal hydroxide self-supporting integrated activated electrode.

2. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 1, characterized in that: The carrier includes at least one of porous metal, porous carbon material and silicon-based material; further includes at least one of foamed nickel, foamed copper, foamed titanium, carbon material, silicide graphene and molecular sieve.

3. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 1, characterized in that: In the metal hydroxide, the types of the metal elements are more than 5; Preferably, the metal M1 includes Fe, Co and Ni; preferably, the molar ratio is 1-4:2-4:2-4.

4. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 1, characterized in that: In the metal hydroxide, the element molar ratio of the metals M1, M2 and M3 is 1-8:1-4:1-4.

5. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 1, characterized in that: Compounding the support and the metal solution of the dissolved metals M1, M2 and M3, followed by drying and alkali precipitation to obtain the electrode precursor; Preferably, in the metal solution, the total metal concentration is 0.1 to 4 M; Preferably, the metal solution is compounded with the carrier by spraying; Preferably, the alkali solution used in the alkali precipitation is an aqueous solution of alkali metal hydroxide; Preferably, the concentration of the alkali metal hydroxide in the alkali solution is above 0.5M; further, 0.5-2M.

6. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 1, characterized in that: Activating the precursor electrode with constant current in an alkaline solution; Preferably, the alkali solution is an aqueous solution of alkali metal hydroxide with a concentration of 0.5M or more, preferably 0.5 to 5M; Preferably, the constant current activation method is a single-electrode, double-electrode or three-electrode method.

7. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 1, characterized in that: The current density during the constant current activation phase was 500 mA / cm 2 Above, further 500mA / cm 2 ~1500mA / cm 2 .

8. The method for preparing the self-supporting integrated activated electrode of multi-metal hydroxide according to claim 7, characterized in that: The time of constant current activation is 10 minutes or longer, preferably 10 to 600 minutes.

9. A self-supporting integrated activated electrode of a multi-metal hydroxide prepared by the preparation method according to any one of claims 1 to 8.

10. An application of a multi-metal hydroxide self-supporting integrated activated electrode prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It is used as an OER catalytic anode for electrocatalysis; Preferably, the electrocatalysis is at least one of aqueous solution electrocatalysis, carbon dioxide electrocatalytic reduction, and nitrogen fixation electrocatalysis; Preferably, the aqueous solution is an alkaline aqueous solution.

Citation Information

Patent Citations

  • Highly sustained electrodes and electrolytes for salty alkaline and neutral water splitting

    CN111936669A

  • Electrocatalytic hydrogen evolution material and preparation method and application thereof

    CN112023926A

  • Alkaline electrolyzed water anode and preparation method thereof

    CN112853392A

  • Preparation method and application of hydroxyl cobalt oxide catalyst

    CN113457679A

  • Oxygen evolution catalytic electrode protected by weak acid salt layer, preparation and application thereof, and method for improving stability of oxygen evolution reaction of oxygen evolution catalytic electrode

    CN113699548A

Cited By

  • Graphite / metal hydroxide composite OER electrode and preparation and application thereof

    CN118910667A

  • Porous single-crystal multi-element alloy catalyst, preparation thereof and application of porous single-crystal multi-element alloy catalyst in HER catalysis

    CN119800420A

  • Porous single-crystalline multi-component alloy catalyst and its preparation and application in HER catalysis

    CN119800420B